Analysis of Brand Loyalty through Brand Image as an Intervening Variable - Arisandi, Edi (Journal of International Conference Proceedings, 2022)
Consumers will judge the quality of a product by experience. A positive experience will result in a positive assessment of the brand that has been used. Companies must maintain a positive consumer experience through the brands. The experience of using a brand will produce opinions, attitudes, and aspects of consumer behavior. A good experience in using a brand will make consumers loyal to the brand; it can impact the company’s sustainability. This study aims to determine the impact of product quality, customer value, and brand experience on brand loyalty through brand image. The sampling method uses non-probability sampling with a purposive sampling method—data retrieval using survey methods. The analysis technique used is Partial Least Square Analysis Structural Equation Modeling (PLS-SEM) using SmartPLS 3. The results are that customer value & brand experience has have a significant effect on brand image, and product quality has no significant effect on brand image & brand loyalty. Customer value has no significant effect on brand loyalty, and brand experience & brand image have a significant effect on brand loyalty. Product quality, customer value, and brand experience have no significant on brand loyalty through brand image.